Binding energy of excitons in parabolic quantum wells in uniform electric and magnetic fields - Taqi, A.; Diouri, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Parameterized equations have been derived using variational calculation for
energy levels of Wannier excitons in 2D-parabolic quantum wells in uniform electric and
magnetic fields. The formulation has been performed in the framework of the effective
mass approximation and two-band model. Illustrations have been given for GaAlAsGaAs-GaAlAs
and CdMnTe-CdTe-CdMnTe parabolic quantum wells. The comparison
with existing data displays good agreement.